(untitled) (Journal of the Medical College for Women & Hospital, 2024)
Background: COVID-19 is a communicable disease caused by severe acute respiratory syndrome corona virus 2. This outbreak has caused a massive stress on vulnerable health care system of developing countries like Bangladesh. Self-medication is very common in our country. It means the use of medicines to treat self-diagnosed symptoms without consulting doctor or physician by the people. Aim: Aim of this study was to assess the prevalence and practice of self-medication during COVID-19 among the medical students. Materials and Method: A descriptive cross sectional study was conducted among the medical students from July to December 2020 by non-probable convenience sampling and data were collected by telephone interview by using semi-structured questionnaire. After completion of data collection, statistical analysis was done using the Statistical Package for the Social Science. Results: The study revealed that prevalence of self-medication was very high among medical students during the pandemic. Students sometimes visited doctor before taking antibiotics and they practiced self-medication because it seems convenient to them. Common symptoms for self-medication were fever, diarrhea, runny nose, cough, nasal congestion, sore throat, aches and pain. Sources of medicines were pharmacy, personal stocks and doctor parents. The relationship between self-medication and year of study, occupation of the father or mother of the respondents, monthly family income were not statistically significant. Conclusion: Self-medication among medical students is very common practice. The study recommends to increase awareness and promote safe practice about self-medication with antibiotics to prevent the emergence of antibiotic resistance and other adverse effects. J Med Coll Women Hosp. 2024; 20 (1) 32-39